An invasive whitefly feeding on a virus-infected plant increased its egg production and realized fecundity. - Jian-Yang Guo (Public Library of Science (PLoS), 2010)
Background Plant-pathogenic begomoviruses have a complex association with their insect vectors. The interactions of begomoviruses and reproduction of their vectors are poorly understood. Bemisia tabaci is known to transmit many begomoviruses, and the spread of B. tabaci, especially the B and Q 'biotypes', has been accompanied by the epidemics of begomoviruses. One of these identified disease-causing agents was Tomato yellow leaf curl China virus (TYLCCNV). Methodology/principal findings In this study, we compared the egg production and realized fecundity of two 'biotypes' or putative species of the whitefly B. tabaci, including the alien invasive B and the indigenous ZHJ1 from Zhejiang, China, feeding on either healthy or TYLCCNV-infected tobacco plants. The ovary of the whitefly was composed of 12-22 telotrophic ovarioles. According to the morphology of the oocytes and level of yolk content, oocytes in ovarioles were divided into four developmental phases (I-IV). Significantly higher proportion of immature oocytes (phase II, III) and mature oocytes (phase IV) was observed in ovary of females that fed on TYLCCNV-infected tobacco compared to that on healthy plants. Moreover, there was significant increase of eggs laid of B whitefly that fed on TYLCCNV-infected tobacco plants during the early developmental stages. In contrast, the proportion of oocytes of different developmental phases and eggs laid had no significant differences between ZHJ1 whiteflies feeding on TYLCCNV-infected and non-infected host plants. Conclusions/significance The invasive B whitefly benefits from feeding on a begomovirus-infected plant through increased egg production and realized fecundity.